MODERN PECULIARITIES OF BANK LENDING TO INDUSTRIAL ENTERPRISES - Herasymenko, Alina (Socio-economic relations in the digital society, 2020)
In economic terms, banks must work closely with the branches of material production. The main task of this partnership is to increase and optimize the use of production and economic potential of industry. Such cooperation has a positive impact on both sides of the partnership and on the socio-economic development of the country as a whole. A common problem of a large number of enterprises in the industrial sector is the outdated material and technical base, which is the «anchor» that restrains their development. Such a state of material and technical base makes it impossible to fully disclose the production and economic potential of enterprises in the industrial sector and hinders the production of competitive products. Thus, the current model of development of domestic industrial enterprises, in general, can be described as a «trap»: against the background of global trends in developed countries (the development of new advanced technologies and innovations, increasing the share of science-intensive industries, the dominance of the fifth technological structure in their structure) domestic industry is based on low-tech production and export of raw materials. Stagnation in the industrial sector is emerging as a new threatening reality. This will have consequences for both the related industries and the financial sector, and especially for banks, as industrial enterprises account for a significant share of banks customer base. The way out of this situation is, first of all, is in providing the appropriate level of funding for the industrial sector. At the same time, modern socio-economic trends contribute to the formation of a special economic environment that has an impact on the current state and conditions of cooperation between banks and industry. The article considers the current situation in the industrial sector of Ukraine, substantiates the need to increase lending to industry by banks, reveals key trends in financing the needs of the industrial sector of Ukraine, and identifies problems and general prospects for bank lending to industrial enterprises.